2020
DOI: 10.1001/jamacardio.2019.5108
|View full text |Cite
|
Sign up to set email alerts
|

Global Differences in Characteristics, Precipitants, and Initial Management of Patients Presenting With Acute Heart Failure

Abstract: IMPORTANCE Acute heart failure (AHF) precipitates millions of hospital admissions worldwide, but previous registries have been country or region specific.OBJECTIVE To conduct a prospective contemporaneous comparison of AHF presentations, etiologic factors and precipitants, treatments, and in-hospital outcomes among global regions through the International Registry to Assess Medical Practice with Longitudinal Observation for Treatment of Heart Failure (REPORT-HF). DESIGN, SETTING, AND PARTICIPANTSA total of 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 42 publications
3
72
1
1
Order By: Relevance
“…Our admission age (64 yrs) is relatively lower compared to high income countries such as the U.S. (73 years) and Western Europe (72 years) as expected, but is in line with other upper middle income countries like Jamaica and Brazil and higher than most countries in Africa and Asia. 32 , 33 , 34 , 35 , 36 , 37 The Hindustani sub-cohort was more frequently admitted for HF admissions, followed by Creole and Javanese which differs slightly from the size of the three largest ethnic groups in Suriname, respectively Hindustani, Tribal communities and Creole. 20 This difference may be partly explained by the differential access of care since the AZP is situated in the capital and people from the rural regions, specifically Tribal and Indigenous communities, may have difficulty accessing AZP health services.…”
Section: Resultsmentioning
confidence: 96%
“…Our admission age (64 yrs) is relatively lower compared to high income countries such as the U.S. (73 years) and Western Europe (72 years) as expected, but is in line with other upper middle income countries like Jamaica and Brazil and higher than most countries in Africa and Asia. 32 , 33 , 34 , 35 , 36 , 37 The Hindustani sub-cohort was more frequently admitted for HF admissions, followed by Creole and Javanese which differs slightly from the size of the three largest ethnic groups in Suriname, respectively Hindustani, Tribal communities and Creole. 20 This difference may be partly explained by the differential access of care since the AZP is situated in the capital and people from the rural regions, specifically Tribal and Indigenous communities, may have difficulty accessing AZP health services.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have also demonstrated higher mortality rates in HF patients with a lower BMI 4 8 . There is a global trend for progressive aging of HF patients 9 , 10 . BMI values are much lower in elderly patients than in younger individuals, and the overlap of aging and low BMI has been most prominently seen in Japan 11 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients hospitalized for HF have a particularly adverse prognosis, with a high risk of mortality and rehospitalization and account for approximately 70% of the total expenditure related to the syndrome. 2 As a result, HF is becoming a major challenge for the health care systems. 3 Several community-based studies and registries have consistently shown that evidencebased therapies are underused in real-life HF patients, while mortality and hospitalization rates are higher than those reported in randomized clinical trials.…”
Section: The Need For a Heart Failure Networkmentioning
confidence: 99%